If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7x+21-x=7(x+3)
We simplify the equation to the form, which is simple to understand
7x+21-x=7(x+3)
Reorder the terms in parentheses
7x+21-x=+(+7x+21)
Remove unnecessary parentheses
+7x+21-x=+7x+21
We move all terms containing x to the left and all other terms to the right.
+7x-1x-7x=+21-21
We simplify left and right side of the equation.
-1x=0
We divide both sides of the equation by -1 to get x.
x=-0
| -16n-2n=16 | | 14=5-2x | | 2(x-5)-8=6+3(x+2) | | 2B=B-10 | | -2.1=y-4.2 | | 2x+5=14+7/3x | | 7y-5.9=8y | | (-3x^2+5)-(5x^2+2x-6)= | | 8(m-3)=36 | | 2x-5=4(x-3) | | 45=9-8x | | 5m+7m=24 | | 3x+2-7x-5=2x+9 | | 7.72x+16=59.5984+4x | | x^2-5x+19=0 | | 5-5n-4=11 | | r^2=24 | | x+2(5+3x)=87 | | 3x=5-4 | | 3x-5+2x=20 | | 12x+5=4x+3 | | 3x-3-4=5 | | r^2-24=0 | | 46+2x=6x+8x+10 | | 1.35m+0.03=7.80 | | y=100x+400 | | 4(6n-4)=128 | | 2m-5=37 | | 4x+18=6x-2 | | 2a+5(a+3)= | | -8(1-7n)=216 | | 3(7x+8)+6(4x+9)=213 |